Know the Mother - Cooper, Desiree (Book collections on Project MUSE., 2016)
Author Desiree Cooper explores the complex archetype of the mother in all of her incarnations. In a collage of meditative stories, women find themselves wedged between their own yearnings and their roles as daughters, sisters, grandmothers, and wives. With her lyrical and carefully crafted prose, Cooper's stories provide truths without sermon and invite empathy without sentimentality.